Increased NT-proBNP levels and cardiac ventricular function during aortic valve replacement (pilot study) - I. A. Kozlov; L. A. Krichevskiy; V. Yu. Rybakov (Вестник анестезиологии и реаниматологии)
The objective was to study the relationship between the increased preoperative N-terminal segment of B-type natriuretic peptide precursor (NT-proBNP) blood levels and the parameters of the heart ventricles function, as well as the conditions for coronary perfusion of their myocardium before and after on-pump aortic valve replacement.Materials and methods. The study involved 27 patients aged 57.7±2.5 years who underwent aortic valve replacement. NT-proBNP blood level was determined before surgery. The level of NT-proBNP > 1000 pg/ml was considered increased. Invasive hemodynamics, including the data of the right ventricle thermodilution volumetry, and transesophageal echocardiography data were analyzed at the stages: the 1st – after anesthesia induction, the 2nd – at the end of surgery. Logistic regression and ROC analysis were used for data processing.Results. Preoperative blood levels of NT-proBNP > 1000 (3163.0[2507.25–7319]) pg/ml were recorded in 55.6% of patients. At the 1st stage, the biomarker increased level was associated with increased index of left ventricular end-systolic volume (OR 1.0955, 95% CI 1.0097–1.1885, p = 0.028, AUC 0.903), decreased left ventricular ejection fraction (OR 0, 9447, 95% CI 0.8949–0.9973, p = 0.040, AUC 0.753) and area contraction fraction (OR 0.8868, 95% CI 0.8086–0.9726, p = 0.011, AUC 0.890), increased mean pulmonary artery pressure (OR 1.1824, 95% CI 1.0020–1.3952, p = 0.047, AUC 0.722), and increased transpulmonary gradient (OR 1.4497, 95% CI 1.0103–2.0802, p = 0.044, AUC 0.810), increased right ventricular stroke work index (OR 1.5151, 95% CI 1.0319–2.2246, p = 0.034, AUC 0.761), and decreased coronary perfusion gradients of the left (OR 0.8961–0.9241, 95% CI 0.8229–0.9459 – 0.8630–0.9896, p = 0.012–0.024, AUC 0.793–0.861) and right (OR 0.9519, 95% CI 0.9136–0.9918, p = 0.019, AUC 0.847) ventricles. At the 2nd stage, NT-proBNP blood values > 1000 pg/ml were associated with impaired left ventricular function, decreased mean arterial pressure (OR 0.9066, 95% CI 0.8264–0.9946, p = 0.038, AUC 0.761), and the vasopressor and inotropic support (OR 8.4000, 95% CI 1.2584–56.0694, p = 0.028, AUC 0.710).Conclusions. Prior to aortic valve replacement, the blood level of NT-proBNP > 1000 pg/ml is associated with a moderate decrease in the left ventricular ejection fraction and area contraction fraction, an increased left ventricular end-systolic volume with a normal end-diastolic volume, an increased index of right ventricular stroke work in combination with moderately increased mean pulmonary artery pressure and increased transpulmonary gradient, as well as a decreased coronary perfusion gradients. At the end of operations, increased NT-proBNP blood level is associated with signs of impaired left ventricular contractility, a tendency to arterial hypotension, and the vasopressor and inotropic support. Increased preoperative NT-proBNP blood level are not associated with right ventricular volumes and ejection fraction both before and after on-pump aortic valve replacement.